Optimizations and recycling industrial waste (palm oil fly ash) as a pigment in coating technology - Mohd @ Mohd Nor, Syarul Hakimi (2017)
In this study, the feasibility of palm oil fly ash (POFA) as a pigment in paint technology is investigated. The utilization of POFA as paint pigment is favorable due to its stability and non-toxicity. On the other hand, producing colour pigment by using POFA as pigment element reduces the solid waste in palm oil industry, in addition to the advantages of inexpensiveness and ready access to POFA feedstock. The objective of this research are to identify the optimum composition of POFA in combination of binder, solvent and additives as pigment in paint, to examine the heat resistant behavior of POFA paint and investigating the POFA paint coating ability to withstand from the paint testing. In general, this research hopes to improve the technology of coating and also can be a significant contribution in the academic, research, development and field studies related to the paint technology. The optimum preparation and thermal conductivity of paint that prepared from the waste of palm oil fly ash (POFA) were investigated. For optimum pigment preparations, the aqueous precursor of 45 % wt POFA mixed with 25 % wt sulphur, 10 % wt graphite fine powder and 20 % wt calcium hydroxide was sintered at 700 – 800 °C to produce a complete crystalline product. The sintered product was milled and become grayish fine powder pigment. From the SEM images, the grain size approximately 0.404 µm. The pigment was mixed with binder, solvent, and additives and grinded to become a paint and tested (glossy test, hardness test, adhesion test, and thermal conductivity test). From the result, the optimum composition of a paint are 22 % wt POFA pigment, 29 % wt binder, 39 % wt solvent and 10 % wt additives (cobalt 10%, lead 32% and N.C Solution). It also discovers that the paint is good insulator with thermal conductivity approximately 78.95 W/m.°C.